Circulating Tumor Necrosis Factor Alpha May Modulate the Short-Term Detraining Induced Muscle Mass Loss Following Prolonged Resistance Training - McMahon, Gerard; Morse, Christopher I.; Winwood, Keith; Burden, Adrian; Onambélé, Gladys L. (Frontiers in Physiology, 2019)
Introduction Tumour Necrosis Factor alpha (TNFα) is a pro-inflammatory cytokine that has been shown to modulate muscle mass, and is responsive to exercise training. The effects of resistance training (RT) followed by a short period of detraining on muscle size, architecture and function, as well as the impact of circulating TNFα levels have not been previously investigated in a young, healthy population. Methods: Sixteen participants (8 males and 8 females) were randomly assigned to a training group (TRG; age 20±3 years, mass 76±7Kg), whilst fourteen participants (7 males and 7 females) age 22±2 years, mass 77±6Kg) were assigned to a control group (CON). Measures of Vastus Lateralis (VL) muscle size (normalised physiological cross-sectional area per Kg body mass; npCSA), architecture (fascicle length; LF, pennation angle Pθ), strength (knee extensor maximal voluntary contraction; KE MVC), specific force, subcutaneous fat (SF) and circulating Tumour Necrosis Factor alpha (TNFα) were assessed at baseline (BL), post 8 weeks RT (PT), and at two (DT1) and four (DT2) weeks of detraining. Results: Pooled BL TNFα was 0.87±0.28pg/mL with no differences between groups. BL TNFα was not correlated with npCSA (p=0.055), KEMVC (p=0.085) specific force (p=0.671) or SF (p=0.995). There were significant (p<0.05) increases in npCSA compared to BL and CON in TRG at PT, DT1 and DT2, despite significant (p<0.05) decreases in npCSA compared to PT at DT1 and DT2. There were significant (p<0.05) increases in LF, Pθ and KE MVC at PT but only LF and torque at DT1. There were no significant (p>0.05) changes in SF, specific force or TNFα at any time points. There was a significant correlation (p=0.022, r 0.57) between the relative changes in TNFα and npCSA at DT2 compared to PT. Discussion: Neither RT nor a period of short term detraining did not alter the quality of muscle (i.e. specific force) despite changes in morphology and function. TNFα does not appear to have any impact on RT-induced gains in muscle size or function, however may play a role in inflammatory-status mediated muscle mass loss during subsequent detraining in healthy adults.